Performance analysis on transmission of multilevel optical pulses using Absolute Polar Duty Cycle Division multiplexing - Malekmohammadi, A.; Mahdiraji, G.A.; Abas, A.F.; Abdullah, M.K.; Mokhtar, M.; Fadlee, M.; Rasid, A. (IEEE, 2008)
In order to explore the potential of optical multilevel signaling for high speed optical fiber networks, an absolute polar duty cycle division multiplexing (AP-DCDM) is demonstrated. Three users, each with the data rate of 10 Gb/s were successfully multiplexed and transmitted over a single WDM channel, which can offer a possible transmission rate of 30 Gb/s per WDM channel. The performance of AP-DCDM technique is examined, with comparison to 30 Gb/s Time Division Multiplexing (TDM) . Back-to-back receiver sensitivity of -29.2 dBm with OSNR of 22.5 dB was achieved for the worst user, together with the chromatic dispersion tolerance ranging from 207 ps/nm to 276 ps/nm. A comparison with conventional TDM technique shows a clear advantage of the proposed AP-DCDM technique.